SELEKSI TANAMAN UMBI-UMBIAN BERDASAR ZAT KIMIA LAHAN MENGGUNAKAN ALGORITMA GENETIK (STUDI KASUS:DI KABUPATEN BANTUL) - Indrianingsih, Yuliani (Sekolah Tinggi Teknologi Adisutjipto, 2017)
This study aims to improve the economic value of farmers' land in the district of Bantul, so that the land has a higher economic value with the appropriate plants. Many farmers are still using self-learning and experience from generation to generation in determining the pattern of plant species, so that the harvest not optimal. So we need a system that can help farmers to determine the type of tuber plants suitable for chemical substances land. The research was conducted in Bantul District for data collection in the field. The results of data collection in the field can be a benchmark for the decision of farmers to determine the type of tuber plants to be planted based on the criteria of soil nutrition. Criteria is a barometer determining the type of tuber is KTK, O, Ca, C / N, Magnesium, Carbon. This research uses genetic algorithm. The results showed that the best tuber plant rank in Bantul Regency was the first rank of red onion, followed by garut bulbs, sweet potato and root talas. Genetic algorithm can be applied for tuber selection in Bantul regency, but has a weakness because it is probabilistic.